Commercial activities in the context of the 19th century subsistence economy in Goiás: Commercial activities in the context of the 19th century subsistence economy in Goiás - Brazil (Revista de História da UEG (REVHIST), 2020)
In this historical article, we discuss some aspects of the commercial activities developed in Goiás in the context of the subsistence economy that was structured after the mining crisis of the late 18th century. Throughout almost the entire 19th century, the word decadence is commonly used by historiography to describe the ruralized and economically disintegrated society that settled in Goiás after the depletion of gold mines. However, even in this context, commercial activities were present and, to a greater or lesser extent, participated in the new economic dynamics of Goiás. The research methodology was based on the bibliographic review, mainly in the contributions of Palacin (1976), Palacin et al (1995), Bertran (1978, 2010) and MCCreery (2006) and in documentary research at the bases of the Historical Geographic Institute of Goiás (IHGG), and of the Lisbon Ultramarine Historical Archive (AHU).Keywords: Goiás. Economy. Subsistence. Trade. XIX century.